Urban Responses to War: The Pact of Free Cities in the Russia-Ukraine Crisis - Anantakupa, Azhar Gusti; Ömer Kutay Seyrek (Universitas Muhammadiyah Yogyakarta, 2025)
This study examined the role of the Pact of Free Cities in responding to the Russia-Ukraine crisis, emphasizing the growing significance of urban paradiplomacy in contemporary international relations. The research addressed the issue of how cities operate as autonomous actors during international crises, independently from their national governments. This topic was considered significant due to the increasing visibility of cities in humanitarian responses and political positioning on the global stage. A qualitative comparative analysis was conducted focusing on the four founding members of the Pact: Warsaw, Prague, Bratislava, and Budapest. The approach involved examining municipal responses to the crisis in relation to their respective national stances. The findings uncovered that Warsaw, Prague, and Bratislava demonstrated alignment between local and national support for Ukraine. In contrast, Budapest’s municipal government adopted a pro-Ukrainian position, diverging sharply from the national government’s pro-Russian orientation. This contrast illustrated the potential of cities to assert independent international positions and contribute meaningfully to global humanitarian and democratic efforts. The study concluded that the Pact of Free Cities has served as a vital platform for cities to uphold democratic values and foster international solidarity, even when national narratives are at odds with one another.